The impact of pre-sowing soybean seed preparation on yield capacity - Kobylynskyi, I.; Аntonets, О. (Scientific Progress & Innovations, 2023)
Soybean cultivation has a stable dynamics to increase both in Ukraine and all over the world taking into account the universality of using this crop in feed production, food and oil production industry. Thus, soybean yield increase becomes topical under limited land resources considering the necessity of decreasing chemical load on the environment, preserving and increasing soil fertility, supplying the population of different countries with food products having a high content of plant protein, etc. The purpose of the article is to study the methods of pre-sowing soybean seed treatment and their effect on the crop yield capacity. Pre-sowing soybean seed treatment is aimed at providing the seeds with the protection from pests and diseases, pathogens in the aggressive soil environment. Such treatment enables to obtain uniform and well-developed seedlings, which directly affects the preservation of varieties’ yield potential. Soybean seeds are treated with inoculants, fungicidal and insecticidal disinfectants, micro-fertilizers, growth stimulants and their mixtures. It is considered that seed treatment with disinfectants is an important prerequisite for obtaining high-quality yield and profitable production as, under such treatment, it is possible to reduce crop losses from 50 to 65 %. The effectiveness of seed disinfection depends on the correct choice of the preparation considering variety characteristics, the forecast of pests and diseases’ affection, and weather conditions. Pre-sowing soybean seed treatment with micro-elements and inoculants enables to increase the number of nitrogen-fixing bacteria nodules, ensure high sowing seed qualities (germination and seed emergence rate), enlarge leaf-area duration, increase individual productivity (the amount of soya beans and seeds per plant, seed weight per plant, thousand-seed weight) and yield, receive a higher content of protein, oil, and cellulose. Pre-sowing soybean seed treatment (especially inoculation) also assists in reducing the expenses on means of chemical protection and increases soil fertility